Effects of Discovery Learning Model Towards Science Process Skills and Learning Retention - Olvyana, Annisa; Ermiana, Ida; Astria, Fitri Puji (Jurnal Pijar Mipa, 2024)
This research aims to determine the effect of the Discovery Learning learning model on science process skills and student learning retention. The population in this study were all 4th-grade students at SDN 6 Cakranegara, totalling 66 students. Samples were taken using a non-probability sampling technique with a saturated sampling type. This research uses a Pretest-Posttest Nonequivalent Control Group Design research design. The instruments used are observation sheets to measure science process skills and multiple-choice test questions to measure learning retention. Analysis in this study used the One-Way ANOVA test with the help of SPSS 21.0 for Windows. The experimental class's average science process skill score was greater than the control class at 77.95%, as was student learning retention at 65%. The statistical analysis results show that the significance value of the influence of treatment on science process skills is 0.000, while the significance value of the influence of treatment on student learning retention is 0.000. So, it can be concluded that H0 is rejected and Ha is accepted, which means a) the discovery learning model influences the science process skills of class IV students, and b) the discovery learning model influences the learning retention of class IV students.